1999
DOI: 10.1111/j.1600-0633.1999.tb00073.x
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and temporal variation in habitat and fish community characteristics in a Kansas Flint Hills stream

Abstract: Four locations (i.e., mouth, lower midreach, upper midreach, and headwater) were sampled bimonthly for two years in a Kansas, Flint Hills stream. Principal components 1 (PCI; depth, width, substrate) and 2 (PC2; velocity, water temperature, conductivity) accounted for 70% of the variation in habitat variables. Principal component 1 varied more spatially than temporally, and PC2 exhibited the opposite pattern. Species diversity varied spatially with the highest values at the upper midreach and mouth and lowest … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…Stream reaches in watersheds that experienced high military training use were dominated by silt-tolerant species and trophic generalists. These results are important because fish communities dominated by trophic generalists and tolerant species are not characteristic of high-quality Flint Hills streams (Tripe andGuy 1999, Schrank et al 2001) and generally indicate a decline in aquatic ecosystem health. In addition, the federally endangered Notropis topeka was only found in reaches with low training use in the watershed and a low proportion of silt substrate, suggesting the importance of watershed recovery for sensitive species.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Stream reaches in watersheds that experienced high military training use were dominated by silt-tolerant species and trophic generalists. These results are important because fish communities dominated by trophic generalists and tolerant species are not characteristic of high-quality Flint Hills streams (Tripe andGuy 1999, Schrank et al 2001) and generally indicate a decline in aquatic ecosystem health. In addition, the federally endangered Notropis topeka was only found in reaches with low training use in the watershed and a low proportion of silt substrate, suggesting the importance of watershed recovery for sensitive species.…”
Section: Discussionmentioning
confidence: 99%
“…The streams of Fort Riley are typical of streams in the Flint Hills, having relatively steep gradients with eroded limestone and shale forming the dominant substrate (Metcalf 1966). Due to the lack of intensive rowcrop agriculture and other large-scale anthropogenic disturbances, most Flint Hills streams have well-developed pool-riffle sequences and large substrates (Tripe and Guy 1999). In addition, Flint Hills streams support the most diverse fish fauna in the Kansas River Basin (Metcalf 1966), and in many streams, the fauna includes threatened and endangered species, such as Notropis topeka.…”
Section: Study Areamentioning
confidence: 99%
“…Furthermore, it has been demonstrated that many fish feed with greater intensity during the periods before and after their reproductive season (BARBIERI et al, 1982;SCHLOSSER, 1982;HARTZ et al, 1996;TRIPE & GUY, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the spatial position within a drainage can greatly influence fish assemblages (Horwitz 1978;Evans and Noble 1979;Matthews 1986;Schlosser 1987;Bhat 2004). The spatiotemporal variation of fish assemblages has been evaluated in warmwater streams in the Midwest (Schlosser 1987), the coastal plains (Adams et al 2004), and the central and southern Great Plains Meador and Matthews 1992;Williams et al 1996;Tripe and Guy 1999;Ostrand and Wilde 2002;Thornbrugh and Gido 2010), and large rivers in the Great Plains (Barko et al 2004;Pegg and McClelland 2004). However, no attempts have been made to describe how fish assemblages in northwestern Great Plains streams vary spatially and temporally or to determine which abiotic factors are important in explaining this spatiotemporal variation.…”
mentioning
confidence: 99%
“…Most studies on the spatiotemporal variation of stream fish assemblages have focused on one stream, one stream and a few of its tributaries, or multiple sites within a stream network (Schlosser 1987;Meador and Matthews 1992;Williams et al 1996;Tripe and Guy 1999;Ostrand and Wilde 2002). However, we are aware of no studies that have assessed the role of watershed size on the spatiotemporal variation of fish assemblages in multiple streams that flow directly into the same river.…”
mentioning
confidence: 99%